Investigation of mixed ion fields in the forward direction for 220.5 MeV/u helium ion beams: comparison between water and PMMA targets - Aricó, Giulia; Gehrke, Tim; Jäkel, Oliver; Mairani, Andrea; Martišíková, Mária (Physics in medicine and biology, 2017)
Currently there is a rising interest in helium ion beams for radiotherapy. For benchmarking of the physical beam models used in treatment planning, there is a need for experimental data on the composition and spatial distribution of mixed ion fields. Of particular interest are the attenuation of the primary helium ion fluence and the build-up of secondary hydrogen ions due to nuclear interactions. The aim of this work was to provide such data with an enhanced precision. Moreover, the validity and limits of the mixed ion field equivalence between water and PMMA targets were investigated. Experiments with a 220.5 MeV/u helium ion pencil beam were performed at the Heidelberg Ion-Beam Therapy Center in Germany. The compact detection system used for ion tracking and identification was solely based on Timepix position-sensitive semiconductor detectors. In comparison to standard techniques, this system is two orders of magnitude smaller, and provides higher precision and flexibility. The numbers of outgoing helium and hydrogen ions per primary helium ion as well as the lateral particle distributions were quantitatively investigated in the forward direction behind water and PMMA targets with 5.2-18 cm water equivalent thickness (WET). Comparing water and PMMA targets with the same WET, we found that significant differences in the amount of outgoing helium and hydrogen ions and in the lateral particle distributions arise for target thicknesses above 10 cm WET. The experimental results concerning hydrogen ions emerging from the targets were reproduced reasonably well by Monte Carlo simulations using the FLUKA code. Concerning the amount of outgoing helium ions, significant differences of 3-15% were found between experiments and simulations. We conclude that if PMMA is used in place of water in dosimetry, differences in the dose distributions could arise close to the edges of the field, in particular for deep seated targets.